FMR1 and AKT/mTOR signaling in human granulosa cells: functional interaction and impact on ovarian response - Rehnitz, Julia; Capp, Edison; Messmer, Birgitta; Nguyen, Xuan Phuoc; Germeyer, Ariane; Freis, Alexander; Dietrich, Jens Erik; Hinderhofer, Katrin; Strowitzki, Thomas; Vogt, Peter H. (Journal of Clinical Medicine, 2021)
We aimed to determine whether a functional link with impact on female ovarian reserve exists between FMR1 expression and expression ratios of AKT/mTOR signaling genes in human granulosa cells in vivo, as suggested from prior in vitro data. Three hundred and nine women, who were classified as normal (NOR; n = 225) and poor (POR; n = 84) responders based on their ovarian reserve, were recruited during stimulation for assisted reproductive techniques. Expressions of FMR1 and of key genes of the AKT/mTOR and AKT/FOXO1/3 signaling pathways were comparatively analyzed in their granulosa cells. FMR1 expression in granulosa cells of NOR and POR correlated significantly with AKT1, TSC2, mTOR, and S6K expression. No correlation was found between FMR1 and FOXO1 in all, and FOXO3 expression in POR, patients. AKT1 expression was significantly higher and FOXO1 expression lower in POR samples, whereas AKT1 expression was lower and FOXO1 expression was higher in NOR samples. In human native granulosa cells, FMR1 expression significantly correlated with the expression of key genes of the AKT/mTOR signaling pathway, but not with the FOXO1/3 signaling pathway. Our data point to a functional link between FMR1 expression and expression of the AKT/mTOR signaling pathway genes controlling human follicular maturation.